2017
DOI: 10.1161/circoutcomes.116.003101
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of a Modified HEART Score in Chest Pain Patients in the Emergency Department

Abstract: Background— The TRAPID-AMI trial study (High-Sensitivity Troponin-T Assay for Rapid Rule-Out of Acute Myocardial Infarction) evaluated high-sensitivity cardiac troponin-T (hs-cTnT) in a 1-hour acute myocardial infarction (AMI) exclusion algorithm. Our study objective was to evaluate the prognostic utility of a modified HEART score (m-HS) within this trial. Methods and Results— Twelve centers evaluated 1282 patients in the emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 49 publications
0
49
1
Order By: Relevance
“…In another recent study, the PLR level was reported to be independently associated with the GENSINI score together with white blood cell (WBC) count, age, and low high-density lipoprotein (HDL) in multivariate analysis [11]. e m-HS includes elements of the history, ECG, age, and risk factors [8]. However, in the original HS, cTn levels were considered in a way that allowed a patient with an elevated cTn to be evaluated as low-risk [8].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another recent study, the PLR level was reported to be independently associated with the GENSINI score together with white blood cell (WBC) count, age, and low high-density lipoprotein (HDL) in multivariate analysis [11]. e m-HS includes elements of the history, ECG, age, and risk factors [8]. However, in the original HS, cTn levels were considered in a way that allowed a patient with an elevated cTn to be evaluated as low-risk [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the original HS, cTn levels were considered in a way that allowed a patient with an elevated cTn to be evaluated as low-risk [8]. In a previous study, it was suggested that when normal serial cTn values are combined with the HS, a very low-risk patient population can be identified, which could be discharged from the ED without further testing [8]. Low-risk patients (a score of ≤3) have been reported to have a low (1.7%) MACE rate [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations